Distinct Expression Patterns of Alveolar "Alarmins" in Subtypes of Chronic Lung Allograft Dysfunction. Issue 6 (1st May 2014) - Saito, T.; Liu, M.; Binnie, M.; Sato, M.; Hwang, D.; Azad, S.; Machuca, T. N.; Zamel, R.; Waddell, T. K.; Cypel, M.; Keshavjee, S.
<x xml:space="preserve">Abstract</x> The long‐term success of lung transplantation is limited by chronic lung allograft dysfunction (CLAD). The purpose of this study was to investigate the alveolar alarmin profiles in CLAD subtypes, restrictive allograft syndrome (RAS) and bronchiolitis obliterans syndrome (BOS). Bronchoalveolar lavage (BAL) samples were collected from 53 recipients who underwent double lung or heart‐lung transplantation, including patients with RAS (n = 10), BOS (n = 18) and No CLAD (n = 25). Protein levels of alarmins such as S100A8, S100A9, S100A8/A9, S100A12, S100P, high‐mobility group box 1 (HMGB1) and soluble receptor for advanced glycation end products (sRAGE) in BAL fluid were measured. RAS and BOS showed higher expressions of S100A8, S100A8/A9 and S100A12 compared with No CLAD (p < 0.0001, p < 0.0001, p < 0.0001 in RAS vs. No CLAD, p = 0.0006, p = 0.0044, p = 0.0086 in BOS vs. No CLAD, respectively). Moreover, RAS showed greater up‐regulation of S100A9, S100A8/A9, S100A12, S100P and HMGB1 compared with BOS (p = 0.0094, p = 0.038, p = 0.041, p = 0.035 and p = 0.010, respectively). sRAGE did not show significant difference among the three groups (p = 0.174). Our results demonstrate distinct expression patterns of alveolar alarmins in RAS and BOS, suggesting that RAS and BOS may represent biologically different subtypes. Further refinements in biologic profiling will lead to a better understanding of CLAD.